(untitled) (Innovative professional education, 2024)
The article presents theoretical and practical aspects of the problem of forming «soft skills» in teachers and students of Professional Pre-Higher Education. Examples of their formation by means of intercultural communication, development and implementation of social projects, continuous development of the teachers’ professional competence are given.